Measurements of gluon-gluon fusion and vector-boson fusion Higgs boson production cross-sections in the H -> WW* -> e nu mu nu decay channel in pp collisions at root s=13 TeV with the ATLAS detector - Onofre, A. (2019)
Higgs boson production cross-sections in proton-proton collisions are measured in the H -> WW*-> e nu mu nu decay channel. The proton-proton collision data were produced at the Large Hadron Collider at a centre-of-mass energy of 13 TeV and recorded by the ATLAS detector in 2015 and 2016, corresponding to an integrated luminosity of 36.1 fb(-1). The product of the H -> WW* branching fraction times the gluon-gluon fusion and vector-boson fusion cross-sections are measured to be 11.4(-1.1)(+1.2)(stat.)(-1.7)(+1.8)(syst.) pb and 0.50(-0.22)(+0.24)(stat.) +/- 0.17(syst.) pb, respectively, in agreement with Standard Model predictions. (C) 2019 The Author. Published by Elsevier B.V.